Effects of individualised positive end-expiratory pressure titration on respiratory and haemodynamic parameters during the Trendelenburg position with pneumoperitoneum: a randomised crossover physiologic trial - Bösing, Christoph; Schaefer, Laura; Schöttler, Jochen; Quentin, Alena; Beck, Grietje; Thiel, Manfred; Honeck, Patrick; Kowalewski, Karl-Friedrich; Pelosi, Paolo; Rocco, Patricia R. M.; Luecke, Thomas; Krebs, Jörg (European journal of anaesthesiology, 2023)
BACKGROUND: The Trendelenburg position with pneumoperitoneum during surgery promotes dorsobasal atelectasis formation, which impairs respiratory mechanics and increases lung stress and strain. Positive end-expiratory pressure (PEEP) can reduce pulmonary inhomogeneities and preserve end-expiratory lung volume (EELV), resulting in decreased inspiratory strain and improved gas-exchange. The optimal intraoperative PEEP strategy is unclear. OBJECTIVE(S): To compare the effects of individualised PEEP titration strategies on set PEEP levels and resulting transpulmonary pressures, respiratory mechanics, gas-exchange and haemodynamics during Trendelenburg position with pneumoperitoneum. DESIGN: Prospective, randomised, crossover single-centre physiologic trial. SETTING: University hospital. PATIENTS:Thirty-six patients receiving robot-assisted laparoscopic radical prostatectomy. INTERVENTION(S): Randomised sequence of three different PEEP strategies: standard PEEP level of 5 cmH2O (PEEP5), PEEP titration targeting a minimal driving pressure (PEEPΔP) and oesophageal pressure-guided PEEP titration (PEEPPoeso) targeting an end-expiratory transpulmonary pressure (PTP) of 0 cmH2O. MAIN OUTCOME MEASURES: The primary endpoint was the PEEP level when set according to PEEPΔP and PEEPPoeso compared with PEEP of 5 cmH2O. Secondary endpoints were respiratory mechanics, lung volumes, gas-exchange and haemodynamic parameters. RESULTS: PEEP levels differed between PEEPΔP, PEEPPoeso and PEEP5 (18.0 [16.0 to 18.0] vs. 20.0 [18.0 to 24.0]vs. 5.0 [5.0 to 5.0] cmH2O; P < 0.001 each). End-expiratory PTP and lung volume were lower in PEEPΔP compared with PEEPPoeso (P = 0.014 and P < 0.001, respectively), but driving pressure, lung stress, as well as respiratory system and dynamic elastic power were minimised using PEEPΔP (P < 0.001 each). PEEPΔP and PEEPPoeso improved gas-exchange, but PEEPPoeso resulted in lower cardiac output compared with PEEP5 and PEEPΔP. CONCLUSION: PEEPΔP ameliorated the effects of Trendelenburg position with pneumoperitoneum during surgery on end-expiratory PTP and lung volume, decreased driving pressure and dynamic elastic power, as well as improved gas-exchange while preserving cardiac output. TRIAL REGISTRATION: German Clinical Trials Register (DRKS00028559, date of registration 2022/04/27). https://drks.de/search/en/trial/DRKS00028559